WOMEN’S INVOLVEMENT IN TERRORISM: A CRITICAL LOOK AT THEIR ROLES IN SELECTED TERRORIST ORGANISATIONS - Agara, Tunde; Subair, Alexander (African Journal of Social and Behavioural Sciences, 2024)
The study examined why societies are slow or not inclined to imbibe the directive on gender equality, as terrorist organisations are using this directive to entice more women by offering them opportunities to hold positions of prominence, which are denied by the societies in which they live. While the research study employed content, process theories and push and pull factors were also examined. The study adopted a multi-layered methodology in which four cases of transnational terrorist groups were selected and qualitatively analysed. The study concludes that women play a variety of roles in terrorist organisations, in some cases more than men do, and the implications of this role for the global war on terror have led to a long way in devising effective counterterrorism strategies and policies. For example, Boko Haram may be abducting girls and women to use as future recruiters or suicide bombers. However, in espionage parlance, they are called ’sleepers’ who can be ’awakened’ later in the future for certain jobs, such as suicide bombing or targeted assassination. Like the Russian KGB, many such ’sleepers’ were deliberately planted in America as American children and families during the heydays of the Cold War.